2012
DOI: 10.1371/journal.pone.0033176
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Chip for Molecular Amplification of Influenza A RNA in Human Respiratory Specimens

Abstract: A rapid, low cost, accurate point-of-care (POC) device to detect influenza virus is needed for effective treatment and control of both seasonal and pandemic strains. We developed a single-use microfluidic chip that integrates solid phase extraction (SPE) and molecular amplification via a reverse transcription polymerase chain reaction (RT-PCR) to amplify influenza virus type A RNA. We demonstrated the ability of the chip to amplify influenza A RNA in human nasopharyngeal aspirate (NPA) and nasopharyngeal swab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 49 publications
(61 reference statements)
1
70
0
2
Order By: Relevance
“…Our data suggest that over-proliferation of astrocytes causes an enlarged brain in GSK-3 mutant mice. Our results are consistent with previous studies that have shown the role of GSK-3 in proliferation of multiple cell types including neural progenitors [11], hematopoietic stem cells [43], pancreatic mesenchymal stem cells [44], fibroblast [45], skin cancer cells [46], and mammary cancer cells [47]. Pharmacological inhibition or genetic elimination of GSK-3 promotes proliferation of these cells.…”
Section: Discussionsupporting
confidence: 93%
“…Our data suggest that over-proliferation of astrocytes causes an enlarged brain in GSK-3 mutant mice. Our results are consistent with previous studies that have shown the role of GSK-3 in proliferation of multiple cell types including neural progenitors [11], hematopoietic stem cells [43], pancreatic mesenchymal stem cells [44], fibroblast [45], skin cancer cells [46], and mammary cancer cells [47]. Pharmacological inhibition or genetic elimination of GSK-3 promotes proliferation of these cells.…”
Section: Discussionsupporting
confidence: 93%
“…4 There have been some reports on performing flow-through PCR for two-temperature thermal cycling inside the microdevice. [5][6][7][8][9][10] Some of them combine the annealing and extension stages at the same temperature region, or the extension region is not created by direct heating but by lateral heat conduction from heaters for denaturation and annealing.…”
Section: Introductionmentioning
confidence: 99%
“…The denaturation and annealing regions were designed to be narrower than the extension region. 10 On conventional layouts with three heating regions, large sized chip modules are required for a suitable arrangement of the microchannel to complete the PCR process. The developed five-temperature-region thermocycler concept overcomes these limitations.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Other detection techniques, such as immunoassays and direct fluorescent antigen testing, are being replaced in favor of the improved sensitivity and shorter turnaround time of PCR. 5 Still, PCR remains relatively expensive due to high reagent costs, and conventional PCR instruments, such as thermoelectric and convective thermocyclers, are limited by large reaction volumes (>5 ll) and thermal inaccuracies. [6][7][8] Further, despite the dozens to hundreds of sample capacities of modern PCR instruments, operation is typically limited to uniform thermal conditions and average reaction durations on the order of 1 h. Yet, different genetic targets have corresponding optimal annealing temperatures that depend on the length and GC content of their primers.…”
Section: Introductionmentioning
confidence: 99%